Леонід Білецький – історик української літератури - Хороб, С.І. (Слово і Час, 2019)
У статті досліджено історико-літературні концепції літературознавчих праць відомого українського вченого з діаспори Леоніда Білецького. На обширному матеріалі його студій з українського письменства, написаних здебільшого в еміграції, їх проаналізовано крізь авторську методологію вивчення ідейно-естетичних явищ національної літератури; виявлено її прикметні риси, специфічні принципи та погляди на існування й розвиток історико-літературного процесу – через факти, зміни, художні персоналії тощо. Для дослідження поставленої мети й завдань використано філологічний, порівняльно-історичний та генетичний методи. Це дало змогу проаналізувати специфіку поглядів Леоніда Білецького як історика національного письменства, починаючи від його навчального підручника “Історія української літератури”, що є своєрідною енциклопедією національної культурно-історичної духовності нашого народу, і завершуючи цілою низкою “портретових історій” багатьох письменників давнього, нового і новітнього українського письменства. The paper deals with historical and literary concepts in the works of the Ukrainian scholar from diaspora Leonid Biletskyi based on the extensive material of his studies on the Ukrainian literature. Using philological, comparative historical and genetic methods the author of the paper analyzes these concepts in the light of Biletskyi’s methodology of studying the ideological and aesthetic phenomena of a national literature that includes revealing characteristic features, specific principles and views on the existence and development of the literary process. This method allows outlining specificity of Leonid Biletskyi as a historian of the national literature, noticeable in his textbook “The History of Ukrainian Literature”, being a kind of encyclopedia of the national cultural and historical spirituality of Ukrainians, as well as in a series of the ‘portrait stories’ presenting many writers of the old, new and contemporary literature. The paper reveals and systematizes historical and literary approaches of the scholar to studying literary and artistic phenomena, processes and certain works. The literary critic evaluated every ideological and aesthetic phenomenon of the national literature based on the general literary criteria. His analysis started from the form (genre, style, stylistics), as, according to the researcher, the form renders the development of the literary process, in which only the core of the author’s artistic thinking – a man and his being – remains unchanged. At the same time Leonid Biletskyi grounded his estimation of the writer’s works and creativity not only on the development of the national literature, but also on the changes in social consciousness of the time. Thus, as a historian of literature, he managed to combine in his scholarly thinking the subjectivity and objective development of the literary process. The historical concepts of Leonid Biletskyi haven’t been studied sufficiently yet. The present paper offers the first review and systematization of them and aims at revealing the special views of the emigration scholar on the development of the Ukrainian literature.